Optimisation of Digital Marketing to Increase Consumer Purchase Interest in the Syar'i Fashion Industry: Case Study on Zahra Bursa Veil Garut - Syafarudin, Dadang; Rahmawati, Tiara Sinthya (Golden Ratio of Data in Summary, 2023)
The development of digital technology has significantly affected the marketing industry, especially in increasing consumer reach and engagement through various online platforms. However, many companies, especially SMEs, have not been able to maximise the potential of digital marketing to increase consumer buying interest. This study aims to examine the effect of digital marketing on consumer buying interest in Zahra Bursa Kerudung Garut, which is engaged in the syar'i fashion sector. This type of research is quantitative with descriptive and associative approaches. The research population consists of consumers of Zahra Bursa Kerudung, with nonprobability sampling techniques and incidental sampling approaches. The research sample totalled 68 respondents. The research location was at Zahra Bursa Veil Garut, and this research took place in 2024. The results showed that the application of digital marketing has a positive effect on consumer buying interest, although its contribution is not entirely dominant, because other factors such as product quality and price also influence purchasing decisions. This research provides important insights into the integration of digital marketing with other aspects in maximising consumer buying interest, especially in SMEs in the shari'i fashion sector. The implication of the results of this study is the importance of optimising innovative digital marketing strategies and improving product and service quality to strengthen relationships with consumers.